2008
DOI: 10.1002/srin.200806322
|View full text |Cite
|
Sign up to set email alerts
|

Components with Optimised Properties due to Advanced Thermo-mechanical Process Strategies in Hot Sheet Metal Forming

Abstract: The increasing demand for car body structures with optimised energy absorption capacity and the ability to maintain their structural integrity even under the highest dynamic load has stimulated the development of new thermo-mechanical process routes for the production of pressed and roll-formed sheet metal parts in order to combine both extreme formability and a highest level of strength for the final product. These process routes offer a high potential for further improvements in the field of strength-strain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(55 citation statements)
references
References 4 publications
0
54
0
1
Order By: Relevance
“…1) However, recently steel parts with martensitic microstructures and more complicated shapes are being produced by hot stamping at temperatures where austenite is stable, followed by die quenching. [2][3][4][5][6] A systematic study of the effect of tempering on sheet tensile specimens of AISI 10B22, a 0.22 wt% C steel, alloyed with boron for hardenability and which corresponds to European grade 22MnB5, has shown that strengths between 1 200 MPa and 1 600 MPa can be produced with little changes in ductility, about 6 to 8 % in sheet tensile specimens, after tempering martensite between 150 to 350°C. 7,8) Tempering at higher temperatures causes extensive discontinuous yielding, greatly reduced strain hardening, and lower strengths.…”
Section: Introductionmentioning
confidence: 99%
“…1) However, recently steel parts with martensitic microstructures and more complicated shapes are being produced by hot stamping at temperatures where austenite is stable, followed by die quenching. [2][3][4][5][6] A systematic study of the effect of tempering on sheet tensile specimens of AISI 10B22, a 0.22 wt% C steel, alloyed with boron for hardenability and which corresponds to European grade 22MnB5, has shown that strengths between 1 200 MPa and 1 600 MPa can be produced with little changes in ductility, about 6 to 8 % in sheet tensile specimens, after tempering martensite between 150 to 350°C. 7,8) Tempering at higher temperatures causes extensive discontinuous yielding, greatly reduced strain hardening, and lower strengths.…”
Section: Introductionmentioning
confidence: 99%
“…The curves in Figure 10 and the data in Table 3 show that, the lower austenitization temperature is helpful for manufacturing the structural components with distributed properties by introducing a thin air gap between the tools and steel plate [26], or using the tool materials with the lower thermal conductivity [27], as the austenite attained at the lower austenitization temperature is particularly susceptible to the cooling rate [28]. The fracture morphology of sample austenitized at 870 °C, 900 °C, 930 °C or 960 °C is shown in Figure 11.…”
Section: Stress and Strainmentioning
confidence: 99%
“…On the other hand, the high tensile strength of the fully hot stamped parts leads to them having low ductility and poor energy absorption characteristics. Such hot stamped parts therefore are not fully optimized for crash performance and light weighting [6][7][8]. Researchers have come up with an innovative solution to this problem where local sheet metal cooling rates are varied by dividing the tooling into heated and cooled zones.…”
Section: Introductionmentioning
confidence: 99%
“…The final microstructure produced in boron steel after tailored hot stamping is a complex mixture of martensite, bainite and ferrite phases depending on the thermal and mechanical processing conditions [1,[6][7][8][9]20]. Metallography and microhardness measurements are well suited for a qualitative assessment of such complex microstructures generated during tailored hot stamping but these techniques are not suitable for quantification of different phases present in the final microstructure.…”
Section: Introductionmentioning
confidence: 99%